Pentingnya Penggunaan Masker Oksigen Pada Pesawat Boeing 737- 400 Saat Keadaan Darurat - Erdiana Finda Ramadhani; Falah Hanun Qatrunnada; Fitra Fakhrizal Davi; Hadi Prayitno; Zainol Mustafa (SKYHAWK : Jurnal Aviasi Indonesia, 2025)
The oxygen mask system on an aircraft is one of the important elements in maintaining the safety of passengers and crew in emergency situations, especially when there is a loss of cabin pressure. This study aims to examine the effectiveness and working mechanism of the oxygen mask system on classic Boeing aircraft, namely the Boeing 737-300, 737-400, and 737-500, during an emergency. The method used in this study is descriptive qualitative, with data collection techniques through interviews, observations, and literature studies. The results of this oxygen mask system study involved various units on the aircraft, including the Passenger Service Unit (PSU), Restroom Service Unit (LSU), and Attendant Service Unit (ASU). Oxygen in the aircraft is supplied from a cylinder through a pressure regulator, and the oxygen mask is automatically released when the cabin pressure drops below a certain threshold. In addition, the oxygen system can also be activated manually by the flight crew. One of the challenges is passenger confusion regarding the correct use of oxygen masks. This study also examines applicable safety regulations as set by the FAA and ICAO, to ensure that the oxygen system functions optimally in an emergency. The study also provides recommendations to improve routine training for cabin crew in handling oxygen mask systems and other safety procedures.